Progesterone‐enhanced sperm hyperactivation through IP3–PKC and PKA signals. (12th September 2012) - Fujinoki, Masakatsu
Abstract: Propose: The present study examined whether regulation of progesterone‐enhanced hyperactivation of spermatozoa is associated with the production of inositol 1, 4, 5‐trisphosphate (IP3 ) and diacylglycerol (DAG) by phospholipase C (PLC) and cyclic adenosine monophosphate (cAMP) by adenylate cyclase (AC), as well as activation of protein kinase C (PKC) and protein kinase A (PKA). Methods: Hamster spermatozoa were hyperactivated by incubation for 4 h in modified Tyrode's albumin lactate pyruvate (mTALP) medium. In order to examine the effects of IP3 receptor (IP3 R), PKC and PKA on progesterone‐enhanced hyperactivation, their inhibitors (xestospongin C, bisindolylmaleimide 1 and H‐89) were used. Results: Progesterone‐enhanced hyperactivation was significantly suppressed by the inhibitors of IP3 R, PKC and PKA. Conclusions: The results suggest that progesterone‐enhanced sperm hyperactivation occurs through two signal pathways. One is an intracellular Ca 2+ signal through production of IP3 and DAG by PLC, binding of IP3 to IP3 R and activation of PKC by DAG and Ca 2+ . The other is a cAMP–PKA signal through production of cAMP by AC and activation of PKA by cAMP.